Deliberate Soccer Practice Modulates Attentional Functioning in Children - Moratal, Consuelo; Lupiáñez, Juan; Ballester, Rafael; Huertas, Florentino (Frontiers in Psychology, 2020)
The main purpose of this study was to explore the association between the regular practice of open skill sports (i.e., soccer) and executive control, along with other attentional functions (i.e., alerting and orienting) during preadolescence. The study was conducted on 131 participants (70 non-athletes and 61 soccer players). To measure cognitive performance, participants performed the Attentional Network Test-Interactions (ANT-I) task. Compared to non-athletes, soccer players showed overall faster responses and better executive control (e.g., reduced interference from distractors). Overall, our results provide new empirical evidence supporting the positive association between regular sports practice and cognitive performance, and more specifically executive functions. However, is important to note that the relationship between regular sport practice and cognition is complex and multifactorial. Our findings can be partly explained by the “cardiovascular fitness hypothesis” and the “cognitive component skills approach”, suggesting that an externally-paced sport environment with high physical fitness and perceptual-cognitive demands may be an appropriate setting to optimize the development of cognitive functioning during early adolescence.